2018
DOI: 10.1186/s12936-018-2476-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asymptomatic Plasmodium infections with sub-microscopic parasite densities in the northwestern border of Thailand: a potential threat to malaria elimination

Abstract: BackgroundAsymptomatic infections with sub-microscopic Plasmodium serve as a silent reservoir of disease, critical to sustaining a low level of remanent malaria in the population. These infections must be effectively identified and targeted for elimination. The sensitivity of light microscopy, the traditional method used for diagnosing Plasmodium infections, is frequently insufficient for detecting asymptomatic infections due to the low density of parasitaemia. The objective of this study was to explore the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…Asymptomatic carriers are individuals who carry the malaria parasites without manifesting any clinical symptoms. However, they remain infectious to mosquitoes and continue to spread the disease [92], and they are potential threat to malaria elimination efforts [93]. It is estimated that 20%-70% of the infections cannot be detected by conventional microscopy and RDTs [94].…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic carriers are individuals who carry the malaria parasites without manifesting any clinical symptoms. However, they remain infectious to mosquitoes and continue to spread the disease [92], and they are potential threat to malaria elimination efforts [93]. It is estimated that 20%-70% of the infections cannot be detected by conventional microscopy and RDTs [94].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effect size was comparatively large with approximately 5-fold higher detectability of infections in high endemic settings compared to low endemic settings. The trend of increasing detectability with increasing transmission intensity may be attributable to the fact that asymptomatically infected individuals have higher average parasite densities in high transmission settings [44,46]. Moreover, in low endemic settings individuals will receive fewer infectious bites with, due to the absence of super-infections, lower parasitemia over the course of infection [40,47].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity of LAMP is several orders of magnitude higher than by microscope and RDT [21] . As worldwide countries set targets of malaria elimination, accurate diagnosis, optimal treatment, stop of transmission, and reducing mortality of malaria are becoming critical [25,26] . As a result of the sudden decline in local patients and the gradual elimination of malaria, there are a trend of degradation in the clinical diagnosis and screening capacity of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, asymptomatic malaria infection and lowdensity malaria parasite emias are hard to be detected by microscope examination and RDT due to below the detection threshold [11,24] , causing misdiagnosis or delayed diagnosis [3,21] . But they could maintaining transmission of malaria as infected intermediate host [24,26] . It has been reported that subclinical malaria accounts for 70-80% of all malaria infections [11] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation